A genetic register for Huntington's chorea in South Wales. Issue 4 (August 1982) - Harper, P S; Tyler, A; Smith, S; Jones, P; Newcombe, R G; McBroom, V
Abstract : A regional genetic register for Huntington's chorea in South Wales is described, based on previous family studies in this area, which is one of high prevalence for the disorder. The primary role of the register is to help in the efficient delivery of services, including genetic counselling, to affected subjects and relatives, and to monitor changes in the population at risk. The mode of operation of the register is described and the essential importance of strict confidentiality is stressed.